2016
DOI: 10.1002/anie.201601003
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Lewis Acid/Cp*CoIII Catalyzed C−H Bond Activation for the Synthesis of Isoquinolin‐3‐ones

Abstract: A facile route toward the synthesis of isoquinolin-3-ones through a cooperative B(C6 F5 )3 - and Cp*Co(III) -catalyzed C-H bond activation of imines with diazo compounds is presented. The inclusion of a catalytic amount of B(C6 F5 )3 results in a highly efficient reaction, thus enabling unstable NH imines to serve as substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(65 citation statements)
references
References 95 publications
0
59
1
5
Order By: Relevance
“…[42] It was necessary to add catalytic amountsoft he strong Lewis acid B(C 6 F 5 ) 3 to promote the transformation more efficiently.O nt he basis of experiments,i ti sp robablet hat B(C 6 F 5 ) 3 plays ad ual role:( i) stabilization of the cationic Co(III) species and (ii)accelerationofthe rates of the C-H activation step and the formation of the Co(III)-carbene intermediate. [42] It was necessary to add catalytic amountsoft he strong Lewis acid B(C 6 F 5 ) 3 to promote the transformation more efficiently.O nt he basis of experiments,i ti sp robablet hat B(C 6 F 5 ) 3 plays ad ual role:( i) stabilization of the cationic Co(III) species and (ii)accelerationofthe rates of the C-H activation step and the formation of the Co(III)-carbene intermediate.…”
Section: Synthesis Of Isoquinolinesmentioning
confidence: 99%
“…[42] It was necessary to add catalytic amountsoft he strong Lewis acid B(C 6 F 5 ) 3 to promote the transformation more efficiently.O nt he basis of experiments,i ti sp robablet hat B(C 6 F 5 ) 3 plays ad ual role:( i) stabilization of the cationic Co(III) species and (ii)accelerationofthe rates of the C-H activation step and the formation of the Co(III)-carbene intermediate. [42] It was necessary to add catalytic amountsoft he strong Lewis acid B(C 6 F 5 ) 3 to promote the transformation more efficiently.O nt he basis of experiments,i ti sp robablet hat B(C 6 F 5 ) 3 plays ad ual role:( i) stabilization of the cationic Co(III) species and (ii)accelerationofthe rates of the C-H activation step and the formation of the Co(III)-carbene intermediate.…”
Section: Synthesis Of Isoquinolinesmentioning
confidence: 99%
“…An illustrative example is the different relay modes identified for two equally effective alkene hydrogenation catalyst systems,[ Rh(PPh 3 ) 3 Cl] (typical dissociative relay mechanism;S cheme 1a)a nd [Rh(PPh 3 ) 3 (CO)H] (hydrideenabled associative covalent relay mechanism;Scheme 1b). [2] In general, the associative relay pathway is difficult to identify because of the tendencyt oe mbrace,e ven without much evidence,t he deceptively simple dissociative relay mechanism.…”
mentioning
confidence: 99%
“…[3][4][5] Despite the great success, at ypical synthetic protocol can only target either the construction of molecular skeletons or the generation of functional appendages,w hich are largely considered two distinct domains of synthesis thus far.W eare interested in the merger of these two types of transformations into as ingle synthetic scheme for the creation of broadly useful functionalgroup-bearing molecular skeletons.I np articular, our initial targets of interest are azaheterocycles containing as ynthetically versatile functionality,aprimary amine.S imultaneous installation of astrongly coordinating functionality along with the generation of amolecular skeleton represents asignificant synthetic challenge because the strongly coordinating functionality can, either alone or together with the directing group,interfere in the target C À Hactivation process.Wehave devised ac yclic surrogate strategy to address both the transition-metal docking and functionality generation issues. [3][4][5] Despite the great success, at ypical synthetic protocol can only target either the construction of molecular skeletons or the generation of functional appendages,w hich are largely considered two distinct domains of synthesis thus far.W eare interested in the merger of these two types of transformations into as ingle synthetic scheme for the creation of broadly useful functionalgroup-bearing molecular skeletons.I np articular, our initial targets of interest are azaheterocycles containing as ynthetically versatile functionality,aprimary amine.S imultaneous installation of astrongly coordinating functionality along with the generation of amolecular skeleton represents asignificant synthetic challenge because the strongly coordinating functionality can, either alone or together with the directing group,interfere in the target C À Hactivation process.Wehave devised ac yclic surrogate strategy to address both the transition-metal docking and functionality generation issues.…”
mentioning
confidence: 99%
“…[4] Position-selective C À Hf unctionalizations of substrates with strongly coordinating N-heterocycles have only very recently been accomplished by means of palladium(II) catalysis with N-methoxy benzamides,aselegantly devised by Dai, Yu,and co-workers ( Figure 1b). [6] Considerable progress was accomplished by the development of high-valent cobalt(III) catalyzed CÀHf unctionalizations, [7] with notable contributions by the groups of Matsunaga/Kanai, [8] Ellman, [9] Chang, [10] Glorius, [11] Shi, [12] Jiao, [13] and Ackermann, [14] among others. [6] Considerable progress was accomplished by the development of high-valent cobalt(III) catalyzed CÀHf unctionalizations, [7] with notable contributions by the groups of Matsunaga/Kanai, [8] Ellman, [9] Chang, [10] Glorius, [11] Shi, [12] Jiao, [13] and Ackermann, [14] among others.…”
mentioning
confidence: 99%
“…[23] Preliminary studies indicated the facile formation of quinazoline 3aa,even in the absence of Cu(OAc) 2 or NaOAc additives (entries 1-4). Among avariety of cocatalytic silver(I) additives,optimal results were obtained with AgSbF 6 (entries [7][8][9][10][11][12]. Among avariety of cocatalytic silver(I) additives,optimal results were obtained with AgSbF 6 (entries [7][8][9][10][11][12].…”
mentioning
confidence: 99%